Quinoa–Peanut Relay Intercropping Promotes Peanut Productivity Through the Temporal Optimization of Soil Physicochemical Properties and Microbial Community Composition in Saline Soil - Xiaoyan Liang; Rao Fu; Jiajia Li; Yinyu Gu; Kuihua Yi; Meng Li; Chuanjie Chen; Haiyang Zhang; Junlin Li; Lan Ma; Yanjing Song; Xiangyu Wang; et al. (Plants)
Peanut productivity is severely restricted by soil salinization and associated nutrient deficiency in saline soil. The quinoa–peanut relay intercrop pattern (IP) is a promising planting system that utilizes the biological advantages of quinoa to improve soil ecological functions and productivity. However, the effects of IP on soil physicochemical and biological properties and the yield formation of the combined peanut crop are still unclear. Two-year field experiments in coastal saline soil were conducted to explore the effects of IP on peanut growth and pod yield, soil physicochemical properties, and microbial community characterization at different growth stages of peanut based on the traditional monocrop pattern (MP). The results show that IP promoted peanut pod yield, although there was the disadvantage of plant growth at an early stage. Soil water content, electrical conductivity (EC), and Na+ content in the peanut rhizosphere were lower, whereas K+, NH4+, and total organic carbon (TOC) contents were higher in IP systems at both the vegetative and reproductive stages. The pod yield of peanut was significantly negatively correlated with soil EC and Na+ contents at the vegetative stage, but positively correlated with K+, NO3−, NH4+, PO43−, and TOC contents at the reproductive stage. IP rebuilt the composition of the soil bacterial community in the peanut rhizosphere and increased the abundance of the beneficial bacterial community, which were positively correlated with soil TOC, K+, NH4+, NO3−, and PO43− contents. These findings suggest that IP can increase peanut pod yield through optimizing soil physicochemical properties and microbial community composition, and it is a promising planting system for improving agricultural production in coastal saline lands.